2015
DOI: 10.1186/s12885-015-1663-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short-term fasting on tolerance to (neo) adjuvant chemotherapy in HER2-negative breast cancer patients: a randomized pilot study

Abstract: BackgroundPreclinical evidence shows that short-term fasting (STF) protects healthy cells against side effects of chemotherapy and makes cancer cells more vulnerable to it. This pilot study examines the feasibility of STF and its effects on tolerance of chemotherapy in a homogeneous patient group with early breast cancer (BC).MethodsEligible patients had HER2-negative, stage II/III BC. Women receiving (neo)-adjuvant TAC (docetaxel/doxorubicin/cyclophosphamide) were randomized to fast 24 h before and after comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
238
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(259 citation statements)
references
References 49 publications
11
238
2
8
Order By: Relevance
“…However, it is not certain whether such effects of fasting on hematopoietic immature cells directly reduce the adverse events of chemotherapy in human patients with various malignancies. The decrease of hemoglobin level by chemotherapy with previous short-term fasting was less in some cases [15] and hematological toxicity was well tolerated following short-term fasting in breast cancer patients [16]. Together with the reduction of gastrointestinal adverse effects of chemotherapy by short-term fasting, such as oral inflammation, nausea, and diarrhea, CR should also have a significantly positive effect on the hematopoietic system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not certain whether such effects of fasting on hematopoietic immature cells directly reduce the adverse events of chemotherapy in human patients with various malignancies. The decrease of hemoglobin level by chemotherapy with previous short-term fasting was less in some cases [15] and hematological toxicity was well tolerated following short-term fasting in breast cancer patients [16]. Together with the reduction of gastrointestinal adverse effects of chemotherapy by short-term fasting, such as oral inflammation, nausea, and diarrhea, CR should also have a significantly positive effect on the hematopoietic system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fasting for 48–140 h before chemotherapy administration in human patients diagnosed with various types of cancer reduced adverse effects, including fatigue, weakness, and gastrointestinal symptoms [15]. The reduction of hematological toxicity following short-term fasting in breast cancer patients [16] suggests that CR has a remarkably positive influence on the hematopoietic system, but the detailed mechanism through which it weakens the adverse events of anticancer drugs is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…All of the preclinical studies summarized in table 1 have confirmed a reduction of side effects from a variety of chemotherapeutic drugs without interfering with, or even boosting, their anti-tumor effects. To date, 3 small studies in humans have also found evidence of a protective effect of STF against chemotherapy-related toxicity [130,131,132]. These studies and their relevance for patients receiving chemotherapy have been discussed in detail elsewhere [133,134,135,136] and will only briefly be reviewed here.…”
Section: Protection Of Normal Cells During Radiotherapymentioning
confidence: 99%
“…In 6 patients who partly had fasted and partly had not, side effects were reduced during those cycles in which chemotherapy had been combined with fasting, in particular fatigue and gastrointestinal problems. The second study, by deGroot et al [131], was a randomized controlled trial in 13 human epidermal growth factor receptor 2 (HER2)-negative stage II and III breast cancer patients who were treated with 6 cycles of combined docetaxel, doxorubicin, and cyclophosphamide. The intervention group who fasted for 24 h prior up to 24 h after chemotherapy administration experienced a significant reduction in IGF-1 levels and lower insulin levels than the control group and exhibited signs of less DNA damage or more efficient DNA double-strand break repair in peripheral blood mononuclear cells [134].…”
Section: Protection Of Normal Cells During Radiotherapymentioning
confidence: 99%
“…Studies of CR in humans have generally addressed cancer treatment [6][7][8][9] but, most recently, carbohydrate-restricted diets, ketogenic diets, and so-called paleo diets which have de facto reduction of carbohydrate (CHO) as a common feature, have shown much promise for prevention [10]. It is understood, however that the discussion has outstripped both understanding of underlying mechanisms and the limited experimental support [11].…”
Section: Introductionmentioning
confidence: 99%